Aesthetic Revolutions and Twentieth-Century Avant-Garde Movements - Erjavec, Aleš (Book collections on Project MUSE., 2015)
This collection categorizes aesthetic avant-garde art as art that seeks to politically transform society and argues that such art is essential for political revolution. It provides seven in-depth analyses of twentieth-century aesthetic avant-garde art movements and examines them in relation to revolutionary politics.